2005
DOI: 10.1111/j.1538-7836.2005.01561.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-derived VWF-cleaving metalloprotease ADAMTS-13

Abstract: Summary. The adhesion ligand von Willebrand factor (VWF) is synthesized and stored in vascular endothelial cells and megakaryocytes/platelets. As in endothelial cells, platelet VWF also contains ultra-large (UL) multimers that are hyperactive in aggregating platelets. ULVWF in platelet lysates of thrombinstimulated platelets was only detected in the presence of EDTA, suggesting that ULVWF is cleaved by a divalent cationdependent protease. A recent study shows that platelets contain the VWF-cleaving metalloprot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
71
1
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 46 publications
2
71
1
6
Order By: Relevance
“…These results indicate that hepatic stellate cells play an important role in the regulation of plasma ADAMTS13 activity, although other sources of ADAMTS13 were reported (14)(15)(16).…”
Section: Introductionmentioning
confidence: 63%
“…These results indicate that hepatic stellate cells play an important role in the regulation of plasma ADAMTS13 activity, although other sources of ADAMTS13 were reported (14)(15)(16).…”
Section: Introductionmentioning
confidence: 63%
“…It encodes a 4.7-kb transcript that is expressed primarily in the stellate cells of the liver and a 2.4-kb transcript detectable in multiple tissues including placenta, skeletal muscle, and certain tumor cell lines (4)(5)(6)(7)(8). Some investigators have reported that ADAMTS13 may also be expressed in platelets and cultured endothelial cells (9)(10)(11). However, this observation remains controversial, and in Northern blotting studies a 4.7-kb band is detectable only in the liver.…”
Section: Pathophysiology Of Ttp Vwf and Adamts13mentioning
confidence: 91%
“…In the liver, ADAMTS13 is expressed primarily in the vitamin A-enriched stellate cells [9;10]. ADAMTS13 may also be expressed in platelets and endothelial cells [11][12][13].…”
Section: Adamts13 -Structure and Functionmentioning
confidence: 99%